Fact and myth of COVID-19 related to nutrition - Saptawati Bardosono (World Nutrition Journal, 2020)
There are no miracle foods or diets that can prevent or cure COVID-19. People are in an anxiety about COVID-19 that makes people more willing to try anything. In fact, to keep people healthy during the COVID-19 pandemic are eat a balanced and varied diet, establish a routine and practice mindful eating, keep hydrated, practice safe food hygiene, stay active at home, get enough quality sleep and last but not least get information from trustworthy source.